Negative pressure breathing: the response of human respiration and circulation to different levels of rarefaction during inspiration - Semenov, Yury S.; Popova, Julia A.; Luzhnov, Petr V.; Demin, Artem V.; Moreva, Tatiana I.; Kriushev, Evgeny S.; Nichiporuk, Igor A.; Dyachenko, Alexander I. (Frontiers in Physiology, 2024)
IntroductionNegative pressure breathing is breathing with decreased pressure in the respiratory tract without lowering pressure acting on the torso. We lowered pressure only during inspiration (NPBin). NPBin is used to increase venous return to the heart and is considered as a countermeasure against redistribution of body fluids toward the head during spaceflight. Aims of our study were: to obtain quantitative information on NPBin-induced changes in parameters of circulation and respiration in healthy human at various rarefactions; to identify main processes involved in cardiorespiratory response to NPBin.MethodsCardiorespiratory response to 25 min of NPBin were studied, rarefaction ranged from −10 to −25 cmH2O. Parameters of systemic, cerebral, and peripheral hemodynamics, as well as respiratory and gas exchange parameters, were measured with non-invasive methods (Finometer, impedance cardiography, rheoencephalography, transcranial Doppler ultrasonography, laser Doppler flowmetry, capillaroscopy). Concentrations of endothelin-1, atrial and brain natriuretic peptides precursors in venous blood, O2 and CO2 tensions in arterialized capillary blood were measured.ResultsTidal volume increased, respiratory rate decreased under NPBin with no significant changes in minute ventilation. Group averaged, respiratory rate and tidal volume changed approximately twice relative to their values observed under normal breathing. Despite the decrease in respiratory rate (up to 2-3 breaths/min), the results indicate CO2 wash-out. Changes in respiratory and gas exchange parameters were virtually independent of rarefaction level. Synchronous with breathing oscillations of circulatory parameters increased in amplitude under NPBin, while values of the parameters averaged over NPBin period changed little. Amplitude of oscillations in parameters associated with arteries virtually did not change with increasing rarefaction. Inspiration under NPBin reduced left ventricle stroke volume and arterial blood pressure, increased heart rate. Head blood filling decreased during inspiration under NPBin, the decrease increased almost linearly with increasing rarefaction. Parameters returned to their initial values after the end of inspiration. Peak-to-peak amplitude of oscillations under NPBin ranged: stroke volume 17–25 mL, mean arterial pressure 7–9 mmHg, heart rate 14–18 bpm. Peripheral hemodynamics responded to NPBin little.ConclusionChanges in stroke volume and central venous pressure during inspiration under NPBin appear to be the major phenomena mediating the effects of NPBin on the cardiorespiratory system.